EFEKTIVITAS KOMITE AUDIT DAN MANAJEMEN LABA RIIL - Yuliani Yuliani; Christine Novita Dewi (Jurnal Riset Akuntansi dan Keuangan, 2015)
h: 0px; "> This research is an empirical study of the audit committee effectiveness towards the company’stendency in conducting real earnings management. The purpose of this research is to obtain empiricalevidence the influence of educational background of the audit committee’s composition, diligence ofthe audit committee, audit committee’s relationship with related parties towards company’s tendencyin conducting real earnings management through sales manipulation, excessive production andreduction in discretionary cost. Sampling was done using purposive sampling method, which uses 117data of manufacturing companies that are listed in BEI (Indonesia Stock Exchange) in the period of2009 to 2012 that tend to conduct real earnings management. The independent variable used are theeducational background composition of the audit committee members, audit committee diligence isproxied by the frequency of the audit committee internal meetings, and the audit committeerelationships with related parties are proxied by the frequency of the external audit committeemeeting, the results showed that the more fulfilled the composition of the audit committee competence,the more numbers of internal and external meetings conducted by audit committee, the lower ofcompany tends to manage their earnings though real activities.Keywords: real earnings management, internal meetings, audit committee’s compositions, externalmeetings